Detection of Cronobacter Genus in Powdered Infant Formula by Enzyme-linked Immunosorbent Assay Using Anti-Cronobacter Antibody - Song, Xinjie; Shukla, Shruti; Lee, Gibaek; Park, Sunhyun; Kim, Myunghee (Frontiers in Microbiology, 2016)
Cronobacter species (Cronobacter spp.) are hazardous foodborne pathogens associated with baby food, powdered infant formula (PIF). To develop a rapid and sensitive method for simultaneous detection of seven Cronobacter spp. in PIF, an indirect non-competitive enzyme-linked immunosorbent assay (INC-ELISA) was developed based on a novel immunoglobulin G (IgG), anti-Cronobacter IgG. The developed INC-ELISA was able to detect seven Cronobacter spp. at concentrations ranging from 5.6×103 to 2.1×105 colony forming unit (CFU)/mL in pure culture. Further, INC-ELISA employing anti-Cronobacter IgG was applicable for analysis of PIF samples contaminated with less than <10 cells of Cronobacter spp. per 25 g of PIF in 36 h. The developed antibody showed slight cross-reactivity with Franconibacter pulveris (LMG 24057) at higher concentration (108 CFU/mL). The INC-ELISA method displayed excellent specificity without compromising cross-reactivity with other foodborne pathogens. The INC-ELISA assay method developed in this study using a novel anti-Cronobacter IgG facilitated highly sensitive, efficient, and rapid detection of Cronobacter spp. in baby food.